THE SERUM COPPER AND ZINC VALUES OF THE SHEEP GROWN UP IN THI_QAR VILLAGES - Jalel abed; Sheren Ali (Basrah Journal of Veterinary Research)
he present study was planned to determine serum Micro mineral status (copper and zinc) of the sheep grown up in Thi_Qar villages .The serum copper &zinc values of the animals were analyzed .with atomic absorption spectrophotometer . The result showed there were non significant differences in all mean serum values of sheep except the mean serum values for animal which showed clinical sings were decrease significantly when compared with other animal which whereby not shown clinical sings .